Case Study Of Shanlian Building Success In Chinese Electrical Appliance Market - Kun, Liu (2008)
Recent shows that China is one of most competitive nations in new millennium and those electrical appliance has become highly developed industry in China within the last 2 decades. The main purpose of this dissertation is to find the right way for those small Chinese electrical appliance companies and those who have experienced in success to achieve more success in the industries.